(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2016)
In Italy, anthracotheres are represented by a few fossils, most of them described during the XVIII centuries and without a standardized scientific method. Anthracotherium monsvialense De Zigno, 1888 was originally erected from a fossil discovered in the site of Monteviale (Vicenza, northeastern Italy), whose Rupelian (MP21) lignitic beds yielded the richest lower Oligocene evidence of the genus Anthracotherium in Europe. A. monsvialense ranges from MP21 to MP23 and its small size has been interpreted as a consequence of the insular environment, at least at Monteviale.In this study, we summarize the long history of Italian findings providing new descriptions of dental and postcranial morphological features of A. monsvialense, and comparing such small anthracothere with its Asian and European relatives. Morphometric analyses are also performed on teeth, in order to verify the presence of evolutionary trends of the genus Anthracotherium.